Diguanylate Cyclase (DGC) Implicated in the Synthesis of Multiple Bacteriocins via the Flagellar-Type III Secretion System Produced by Pectobacterium carotovorum subsp. carotovorum - Lagitnay, Ruchi Briam James Sersenia; Chen, Han-Ling; Chen, Yen-Chun; Chuang, Duen-Yau (International journal of molecular sciences, 2022)
The plant pathogen Pectobacterium carotovorum subsp. carotovorum (previously Erwinia carotovora subsp. carotovora) causes soft rot and stem rot diseases in a variety of crops, including Chinese cabbage, potato, and tomato. The flagellar-type III secretion systems were used by Pcc’s virulence mechanism to export proteins or bacteriocins to the outside of the cell. DGC, a virulence factor that cyclizes c-di-GMP, a common secondary signal in physiological processes and toxin control systems of many bacteria, was discovered in Pcc’s genomic DNA. The dgc gene in Pcc was blocked using the method of homologous recombination in our study. In the in vivo setting, the results demonstrated that the dgc knockout strain does not release low molecular weight bacteriocins. The bacteriocin gene (carocin S2, carocin S3, carocin S4) and the flagellar-type III secretion system genes were also unable to be transcribed by the dgc knockout strain in the transcription experiment. We also observed that the amount of bacteriocin expressed changed when the amount of L-glutamine in the environment exceeded a particular level. These data suggested that L-glutamine influenced physiological processes in Pcc strains in some way. We hypothesized a relationship between dgc and the genes involved in Pcc LMWB external export via the flagellar-type secretion system based on these findings. In this study, the current findings led us to propose a mechanism in which DGC’s cyclic di-GMP might bind to receptor proteins and positively regulate bacteriocin transcription as well as the synthesis, mobility, and transport of toxins.